Breaking through - Liautaud, Martine, 1950- 4 0 16; 5 (Hoboken, NJ : Wiley, 2016)
When women succeed, we all win. Breaking Through explores the mentoring relationship, and unravels its effects on women, businesses, society, and the economy. In 2010, author Martine Liautaud founded the Women Business Mentoring Initiative (WBMI) to support women entrepreneurs with the targeted advice and personalized guidance that can only come from a mentor. In late 2015, she set up the Women Initiative Foundation to broaden her action in favor of women in the business world. This book encapsulates the WBMI mission and other similar experiences inside international and US corporations, showing how mentoring and sponsorship can take many forms-and how each form benefits women in business. Through evidence-based narratives, you'll learn what real women have gained from both sides of the dynamic, and why they credit mentoring with the strength of their business success. These stories show how mentoring yields increased efficiency, improved financials, more effective management, increased innovation, a broader talent pool, and increased revenues, and how helping women succeed in business leads to increased philanthropy and improves community sustainability. Gender equality has made huge strides in the US and Western Europe, but this progress is only apparent in the junior levels of the workplace. This book shows how mentoring women entrepreneurs and women managers provides the key that opens the door to the new economy. Understand why mentoring is key to women's economic advancement Learn how mentoring yields tangible benefits beyond the workplace Delve into the experiences of real mentor/mentee pairs Consider the effectiveness of various types of mentoring Despite the increasing opportunities for women in business, statistics and pervading stereotypes suggest that true gender equality is still far on the horizon. Mentoring and sponsorship can be tremendously helpful to women looking to achieve great things-the wisdom of experience is a powerful asset in business strategy and decision-making, and the mentor/mentee relationship benefits everyone. Breaking Through makes a compelling case for the effectiveness of mentoring, with real women's stories of success--;This book provides evidence-based narratives of the various types of mentoring and their degrees of success--
French Retail Banking BNP Paribas as a Proactive Supporter of Women in Business: A Mentoring Program Chapter 14 Women's Initiative Network and Reverse Mentoring Program Interview with Karen Peetz, President of BNY Mellon Interview with Jean Wynn, Managing Director and Chief Administrative Officer of BNY Mellon's Office of the President Part IV Mentoring Program Success Stories Chapter 15 BNP Paribas Corporate & Institutional Banking (CIB) Interview Tabitha Coombe (Mentee) Interview with François Freyeisen (Mentor) Interview with Siobhan Roche (Mentee) Interview with Constance Chalchat (Mentor) Chapter 16 ENGIE Interview with Mathias Curnier (Mentor) Interview with Paola Vezzaro (Mentee) Chapter 17 Oracle Interview with Nicoleta Apostol (Mentee) Interview with Giovanna Sangiorgi (Mentor) Interview with Paula Craythorne (Mentee) Chapter 18 Publicis Groupe Interview with Michele Gilbert (Mentor) Interview with Charlotte Guillabert (Mentee) Chapter 19 BNY Mellon Interview with Regina Meredith-Carpeni (Mentor) Interview with Yoon Park (Mentor) Interview with Jeff KUHN (Mentee) Part V Ways to Help Entrepreneurs to Succeed Chapter 20 Mentoring and Sponsoring Programs Mentoring Women Entrepreneurs Interview with Emilie Creuzieux, Founder of Monbento (Mentee) Interview with Jean-Jacques Berard, Co-founder of Executive Interim Management (Mentor) Interview with Muriele Roos, Founder of Femme Majuscule (Mentee) Interview with Eve Magnant, VP at Publicis (Mentor) Interview with Jane Chen, Co-founder of Embrace (Mentee) Interview with Abigail Holsborough, Founder of RouteMap (Mentee) Interview with Clara Shih, Founder of Hearsay Social (Mentee) Chapter 21 Networking Dell Women's Entrepreneur Network (DWEN) ASTIA -- A Different Kind of Network Performing in a Different Kind of Way The Goldman Sachs '10,000 Women' Initiative Chapter 22 Training Women Entrepreneur Program in Stanford.
Includes index.
Print version record.
Keywords: 2 -- 0; 6; Businesswomen.;Leadership.;Sex discrimination against women. -- 20; 20; Electronic books. -- 2